Object management in distributed database systems for stationary and mobile computing environments a competitive approach - Lin Wujuan; Veeravalli Bharadwaj (Boston Kluwer Academic, 2003)
It presents a specialized topic in the area of database management. It's organized into 7 chaps. Chap 1 explores about DDBS from different aspects; Chap 2 deals a general approach to the entire object management process and their applications focusing Hi
Keywords: Distributed databases